Improving organisational resilience to disaster events: an FM perspective - Keith Jones; Femke Mulder; Mariantonietta Morga; Nadeeshani Wanigarathna (2022)
Background and aim - Improving the resilience of business organisations and critical infrastructure providers to disaster events is a major challenge facing many European organisations. Recent floods in Germany, Belgium and the Netherlands and earthquakes in Iceland, Italy, Romania and Greece have demonstrated the need for organisations to adopt a holistic view of their vulnerabilities, adaptive capacities and resilience planning. This paper focuses on the role that facilities managers could play in the development of disaster management and business continuity and resilience plans. Methods / Methodology - The paper draws on data collected through an interpretivist, observational action research study to identify the key factors that affect organisational resilience to earthquakes. Literature reviews, interviews and workshops with end-user stakeholder organisations were used to identify physical and operational mitigation interventions that could help organisations better prepare for, absorb and recover from an earthquake. Results - The paper presents a hierarchical model of organisational resilience and a generic resilience assessment and risk management framework that can help organisations better understand and manage their disaster risks. The paper delineates the role of facilities managers in assessing the impact that the disaster risks could have on hard and soft facilities management and in identifying mitigation interventions to support primary service or product delivery following a disaster event. Practical or social implications - The paper makes a valuable contribution to the literature on organisational resilience to disaster events by highlighting the little researched role of facilities management in this context. Type of paper - Research paper (full).